Interannual and Seasonal Variability of Macroinvertebrates in Monsoonal Climate Streams - Mesa, Leticia Mariana (2012)
The aim of this study was to assess the interannual and seasonal changes in the community composition, abundance and presence-absence of macroinvertebrates in the streams of the northwestern of Argentina. The importance of environmental variability in determining these changes was also analyzed. Macroinvertebrates were collected in eleven streams during high (March) and low (September) water periods during two years. Physical variables and water parameters were also recorded at each site. Community composition and abundance differed significantly between seasons, but the presence-absence data did not exhibit a clear pattern of seasonal change. Rapid recolonization of disturbed substrate could ensure the recuperation of benthic community. Small body sizes, short life cycles and continous reproduction could be important strategies that ensure the rapid resilience and persistence of macroinvertebrate assemblages in time.